Standardized Health data and Research Exchange (SHaRE): promoting a learning health system. Issue 1 (17th January 2022) - Davis, Sierra; Ehwerhemuepha, Louis; Feaster, William; Hackman, Jeffrey; Morizono, Hiroki; Kanakasabai, Saravanan; Mosa, Abu Saleh Mohammad; Parker, Jerry; Iwamoto, Gary; Patel, Nisha; Gasparino, Gary; Kane, Natalie; et al.
Abstract: Aggregate de-identified data from electronic health records (EHRs) provide a valuable resource for research. The Standardized Health data and Research Exchange (SHaRE) is a diverse group of US healthcare organizations contributing to the Cerner Health Facts (HF) and Cerner Real-World Data (CRWD) initiatives. The 51 facilities at the 7 founding organizations have provided data about more than 4.8 million patients with 63 million encounters to HF and 7.4 million patients and 119 million encounters to CRWD. SHaRE organizations unmask their organization IDs and provide 3-digit zip code (zip3) data to support epidemiology and disparity research. SHaRE enables communication between members, facilitating data validation and collaboration as we demonstrate by comparing imputed EHR module usage to actual usage. Unlike other data sharing initiatives, no additional technology installation is required. SHaRE establishes a foundation for members to engage in discussions that bridge data science research and patient care, promoting the learning health system.